Transcriptome-wide miRNA identification of Bacopa monnieri: a cross-kingdom approach. (2nd January 2020) - Gadhavi, Harshida; Patel, Maulikkumar; Mangukia, Naman; Shah, Kanisha; Bhadresha, Kinjal; Patel, Saumya K.; Rawal, Rakesh M.; Pandya, Himanshu A.
ABSTRACT: Bacopa monnieri known as 'Brahmi' is a well-known medicinal plant belonging to Scrophulariaceae family for its nootropic properties. To the best of our knowledge, no characterization data is available on the potential role of micro RNAs (miRNAs) from this plant till date. We present here the first report of computational characterizations of miRNAs from B. monnieri . Owing to the high conservation of miRNAs in nature, new and potential miRNAs can be identified in plants using in silico techniques. Using the plant miRNA sequences present in the miRBase repository, a total of 12 miRNAs were identified from B. monnieri which pertained to 11 miRNA families from the shoot and root transcriptome data. Furthermore, gene ontology analysis of the identiﬁed 68 human target genes exhibited significance in various biological processes. These human target genes were associated with signaling pathways like NF-kB and MAPK with TRAF2, CBX1, IL1B, ITGA4 and ITGB1BP1 as the top five hub nodes. This cross-kingdom study provides initial insights about the potential of miRNA-mediated cross-kingdom regulation and unravels the essential target genes of human with implications in numerous human diseases including cancer.